Effectiveness of a pre-licensing driver education program on five psycho-social factors over twelve months. (December 2020) - Bates, Lyndel; Evenhuis, Amanda; Lennon, Alexia
Highlights: Pre-licence driver education is mandatory for new drivers in the Australian Capital Territory. Young novice driver sensation seeking and optimism bias increased between pre and 9–12 months post the education course. Illusionary invulnerability and differential association decreased over this period. Results indicate that the program has only limited effect on psychosocial factors. Abstract: A pre and post (1, 4, and 9–12 months follow up) survey of psychosocial variables was used to examine the effect of a compulsory pre-licence driver education program for drivers aged 16–20 years, in the Australian Capital Territory. While the final survey was collected by telephone, all other surveys were completed online. Two-way mixed ANOVAs revealed that sensation seeking and optimism bias increased over time while illusionary invulnerability and differential association fell. Participants perceived driving as more risky 9–12 months after completing the course compared to their views prior to the course. These results suggest that the program may have a limited effect on these five psychosocial factors over time. Policy makers may need to carefully consider the reasons for providing driver education, the optimal time during the licensing process to provide this education, and the financial and social costs of doing so.